Kedudukan Keuntungan Usaha Pra-Perkawinan sebagai Harta Bersama dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Adam Ramadhan; Muhammad Zaky (Esensi Hukum, 2025)
This study examines the legal issue concerning the status of profits generated from a business owned prior to marriage, specifically whether they constitute separate property or joint marital property. Although the business itself is classified as separate property, the profits generated during the marriage are frequently tied to the spouse's contributions, leading to differing interpretations in both Islamic law and Indonesian positive law. This research aims to analyze the regulations governing joint property in relation to pre-marital businesses and assess the relevance of the North Jakarta Religious Court Decision Number 2596/Pdt.G/2025/PA.JU to the development of law in Indonesia. Utilizing a normative legal research method with statutory, conceptual, and case approaches, the primary legal materials examined include Law No. 1 of 1974 concerning Marriage (as amended by Law No. 16 of 2019), the Compilation of Islamic Law, and relevant court decisions, supported by secondary legal materials from academic literature. The findings conclude that, in principle, a pre-marital business retains its status as separate property. However, the profits acquired during the marriage can be categorized as joint marital property if there is proven, tangible contribution from the spouse in supporting the sustainability and development of the business. Decision Number 2596/Pdt.G/2025/PA.JU reflects a progressive development in legal interpretation, wherein judicial considerations are no longer strictly confined to the time of asset acquisition but also accommodate economic value growth and the contributions of both parties. Therefore, this decision holds significant relevance in filling regulatory vacuums and encouraging the reform of joint marital property law in Indonesia to be more oriented towards substantive justice. Keywords: Marital Property, Separate Property, Profits From Pre-Marital Business, Islamic Law, Indonesian Positive Law